1999
DOI: 10.1097/00003072-199909000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Cerebral Hypoperfusion Observed With Tc-99m HMPAO SPECT in Reversible Dementia Caused by Hypothyroidism

Abstract: A 69-year-old man had hypothyroid dementia as a result of I-131 therapy and an overdose of methimazole. Tc-99m HMPAO SPECT revealed diffuse cerebral hypoperfusion. The findings of brain SPECT normalized with the disappearance of symptoms and a return to the euthyroid state. There was a 25% or 26% reduction of the mean cerebral blood flow during dementia. This may be the first report in which SPECT brain imaging revealed reversible hypoperfusion associated with reversible hypothyroid dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…Impaired brain perfusion in patients with known autoimmune thyroiditis has been demonstrated and supports a hypothesis of cerebral involvement in autoimmune thyroiditis [7,8,9]. However, a recent study showed that a 6-month levothyroxine treatment reduces systemic inflammation in patients with Hashimoto's thyroiditis.…”
Section: Discussionmentioning
confidence: 90%
“…Impaired brain perfusion in patients with known autoimmune thyroiditis has been demonstrated and supports a hypothesis of cerebral involvement in autoimmune thyroiditis [7,8,9]. However, a recent study showed that a 6-month levothyroxine treatment reduces systemic inflammation in patients with Hashimoto's thyroiditis.…”
Section: Discussionmentioning
confidence: 90%
“…Some have reported diffuse global hypoperfusion [8789] while others demonstrated decreased regional cerebral blood flow [90–92]. Furthermore, variable findings regarding restoration of blood flow with treatment have been documented.…”
Section: Neuroimaging In Thyroid and Mood Disordersmentioning
confidence: 99%
“…We note that other case reports have described white matter frontal lobe changes on MRI of the brain similar to the findings in our patient 8. In addition, positron emission tomography and single photon emission CT studies have revealed a generalised decrease in cerebral perfusion and glucose metabolism in hypothyroid subjects, which may be reversible with treatment 9 10. Meanwhile, a reversible reduction in wave activity on electroencephalogram has also been associated with hypothyroidism with psychiatric manifestations 11…”
Section: Discussionmentioning
confidence: 99%